(untitled) (Indian Journal of Animal Production and Management, 2024)
A total of 20 piglets (10 castrated males and 10 females) at 3 months of age with initial body weight of 18.94 ± 1.04 Kg were randomly subjected to minimum limit of floor area recommendations of housing standards (IS: 3916-1966) range of 0.9-1.8 square meter for weaner to finisher. In treatments Tc, pigs were provided with only 0.9 m2 covered floor area per pig without access to open area and in control (To) with covered floor area of 0.9 m2 plus additional equal open floor area (total 1.8 m2 per pig). Result showed that resource use efficiency in terms of saving of 90 % space, 41.23 % labor and 22.05 % water per pig in Tc were significantly (p < 0.01) better than To. However, production cost per kg live weight in Tc was 5.38 % higher than To.